Biochemical engineering and biotechnology - Najafpour, Ghasem D. (Amsterdam, Netherlands : Elsevier, 2015)
Biochemical Engineering and Biotechnology, Second Edition outlines the principles of biochemical processes and explains their use in the manufacturing of everyday products. The text covers the major concepts of biochemical engineering and biotechnology, and is an ideal reference for chemical engineering students who need to learn and apply biological knowledge in engineering principles. The author takes a direct, useful approach in presenting the concepts and practical applications, including many solved problems, case studies, examples, and demonstrations of detailed experiments, with simple design equations and required calculations also included. It is ideal for both those interested in more advanced research in the field of biotechnology, also acting as a guide for beginners seeking direction on establishing research in this field.
3.13.5 KINETIC OF WATER GAS SHIFT REACTION3.14.6 GROWTH KINETICS OF CO SUBSTRATE ON C. LJUNGDAHLII; NOMENCLATURE; Acknowledgments; References; Chapter 4 -- Fermentation Process Control; 4.1 INTRODUCTION'THIS CASE STUDY WAS PARTIALLY WRITTEN WITH CONTRIBUTIONS FROM:HOSSEIN ZARE, BIOTECHNOLOGY RESEARCH LAB., FACU ... ; 4.2 BIOREACTOR CONTROLLING PROBES; 4.3 CHARACTERISTICS OF BIOREACTOR SENSORS; 4.4 TEMPERATURE MEASUREMENT AND CONTROL; 4.5 DISSOLVED OXYGEN MEASUREMENT AND CONTROL; 4.6 PH/REDOX MEASUREMENT AND CONTROL; 4.7 DETECTION AND PREVENTION OF FOAM; 4.8 BIOSENSORS; NOMENCLATURE; References; Chapter 5 -- Growth Kinetics.
Includes bibliographical references at the end of each chapters and index.
Description based on online resource; title from PDF title page (ebrary, viewed March 5, 2015).
Elsevier
Keywords: Biochemical engineering; Biotechnology; Biochemical engineering; Biotechnology -- Methods; Biotechnology; Biochemical engineering; Biotechnology; Electronic books; Electronic books